1985
DOI: 10.1073/pnas.82.18.6211
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of kappa chain constant region genes in mouse lambda chain-producing B cells involve intrachromosomal DNA recombinations similar to V-J joining.

Abstract: We isolated and characterized the germ-line counterpart of a DNA segment designated RS (for recombining sequence), that is frequently recombined in mouse X light chain-producing B lymphocytes. Using Southern blot analyses of myelomas and mouse-Chinese hamster fusion cell lines, we found that RS DNA sequences are located on mouse chromosome 6, evidently more than 15 kilobases downstream of the K light-chain locus. We find that a typical recognition site for Ig gene recombination is situated within germ-line RS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…We also recovered V -RS rearrangements at the wt allele in four members of group C using primers specific for RS and the V framework 3 region. Thus, expression of V x in the 56RV 8 B cell hybridomas was found to correlate with a RS-mediated deletion of C at the V 8 allele, consistent with earlier findings that -expressing B cells frequently show RS-mediated deletions of C (57,58). Rearrangements involving RS were also observed in four of seven V 21D-expressing hybridomas (Table III).…”
Section: Analysis Of L Chain Gene Rearrangements In 56rv 8 Splenic B supporting
confidence: 77%
See 1 more Smart Citation
“…We also recovered V -RS rearrangements at the wt allele in four members of group C using primers specific for RS and the V framework 3 region. Thus, expression of V x in the 56RV 8 B cell hybridomas was found to correlate with a RS-mediated deletion of C at the V 8 allele, consistent with earlier findings that -expressing B cells frequently show RS-mediated deletions of C (57,58). Rearrangements involving RS were also observed in four of seven V 21D-expressing hybridomas (Table III).…”
Section: Analysis Of L Chain Gene Rearrangements In 56rv 8 Splenic B supporting
confidence: 77%
“…7B). Thus, all seven hybridomas (B1-7) that secreted IgM a molecules cross-reactive with AF6-78 anti-IgM b (shown in Table II) IgM a -expressing hybridomas were also examined for rearrangements involving the RS element downstream of the C constant region gene (57,58). Using primers specific for the V 8 leader, J C intronic recombining sequence (IRS1) and RS (see Materials and Methods), we recovered PCR products corresponding to an IRS1-RS rearrangement at the tg allele in all V x-expressing hybridomas of group C (Table III).…”
Section: Analysis Of L Chain Gene Rearrangements In 56rv 8 Splenic B mentioning
confidence: 99%
“…The nonproductive allele has a V-J 5 and so cannot undergo further V-J recombination; however, RS rearrangements were observed at the nonproductive allele in three of eight clones analyzed. RS rearrangements were originally thought to be a last resort recombination event leading to deletion of the C region before V(D)J rearrangements at the locus (33). We found that all 38C-13 variants with an RS rearrangement had a V-J 4 rearrangement on the productive allele.…”
Section: Discussionmentioning
confidence: 56%
“…However, deletion of the nonproductive allele could be the result of RS rearrangement. RS rearrangements, which were first observed in -producing B cells, are V(D)J recombinase-dependent rearrangements that inactivate the locus by deletion of either the C exon or the entire J -C region (33). As shown schematically in Fig.…”
Section: C-13 Cells Undergo Rs Rearrangementsmentioning
confidence: 99%
“…B cells expressing X L chains have frequently rendered one or bothJx alleles nonfunctional by the rearrangement of a recombining sequence (RS)' element (9)(10)(11) . The RS element lies 3' of the mouse Cx exon and is bordered at its 5' side by a 23-bp heptamer nonamerjoining signal (9,10).…”
mentioning
confidence: 99%